Pemanfaatan Limbah Penggergajian Kayu Meranti Merah Sebagai Bahan Baku Papan Partikel Kerapatan Sedang Dengan Perekat Alami Asam Sitrat: Utilization of the Red Meranti Sawmill Waste for Raw Material of Medium Density Particleboard with Citric Acid Natural Binder - Desy Natalia Koroh; Mahdi Santoso; Fitri Diana Batubara; Milad Madiyawati; Nuwa Nuwa (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
Red Meranti was a commercial wood that is widely used as a raw material for the timber industry (plywood and sawmill industry), and generated a lot of waste. Currently, the utilization of red meranti waste has not been utilized optimally. One of the optimizing utilization of that waste was for developing a Particleboard with the citric acid natural binder. The objective of this study was to determine the bonding properties of Sawmill Waste Red Meranti Particleboard bonded with a Citric Acid Natural Adhesive. Citric acid was dissolved in water with the concentration of the solution adjusted to 60 wt%. This adhesive solution was sprayed onto the 40 mesh (coarse) and 40 mesh (fine) particles at 10% and 20% resin content based on the weight of oven-dried particles. Each mixture was then hot pressed at 110°C for 15 min under 50 kg/cm² pressure. Density and dimension targets were 0.7 kg/cm³; 30 × 30 × 1 cm. Each experiment was performed in triplicate, and the average value and standard deviation were calculated. The results showed that the interaction of particle size and adhesive content had a very significant effect on density, internal bonding, and screw-holding strength and had no significant effect on moisture content, thickness swelling, and modulus of rupture (MOR). Based on the SNI 03-2105-2006, the physical properties that meet the standard were moisture content and. Meanwhile, the mechanical properties of sawmill waste red meranti particleboard have not met the SNI 03-2105-2006. Kata kunci (Keywords): Sawmill waste, red meranti waste, citric acid, natural binder.